ANALISIS SISTEM ANTRIAN DAN OPTIMALISASI PELAYANAN (Studi Kasus pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Surakarta) - Eva Nur Safitri; Amin Wahyudi; Erni Widajanti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the model and characteristics of the queue system and analyze service optimization throught queue analysis in the employment service process at BPJS Ketenagakerjaan Surakarta. The type of data used is quantitative data and qualitative data. Data sources used are primary data and secondary data. The population in this study were BPJS Ketenagakerjaan Surakarta customers who came and queued to get service. The sampling technique uses non probability sampling techniques by using paul leddy formula as manis as 100 customers. Data analysis technique use queuing model formula, software microsoft exel, sosftware SPSS 21, and software QM for windows. The results of the study show that the queuing model that is applied in the service process of document inspection and service stages uses the M/M/S model. Queue characteristic in the service process have a random arrival pattern and FIFO queue discipline so that customers who come first will be served first. The result of the analysis of the queuing system indicate that there is a nedd to add customer service to the first stage of service facilities namely the document checking stage because the results of the queuing system analysis result show a negative value while in the second stage of service proces namely the service stage shows that the services performed are optimal.